Acute Freeze-Dried Mango Consumption With a High-Fat Meal has Minimal Effects on Postprandial Metabolism, Inflammation and Antioxidant Enzymes. (August 2019) - O'Hara, Crystal; Ojo, Babajide; Emerson, Sam R; Simenson, Ashley J; Peterson, Sandra; Perkins-Veazie, Penelope; Payton, Mark E; Hermann, Janice; Smith, Brenda J; Lucas, Edralin A
Objective: Postprandial fluxes in oxidative stress, inflammation, glucose, and lipids, particularly after a high-fat meal (HFM), have been implicated in the development of cardiovascular disease (CVD). The aim of this study is to determine whether acute freeze-dried mango consumption modulates the postprandial response to an HFM. We hypothesized that the addition of mango, which is a rich source of many bioactive components, to an HFM would lower postprandial triglycerides, glucose, and inflammation, and increase antioxidant enzymes, compared to a standard HFM alone. Methods: In a randomized cross-over study, 24 healthy adult males (18-25 years old) consumed a typical American breakfast (670 kcal; 58% fat) with or without the freeze-dried mango pulp (50 g). Lipids, glucose, antioxidant enzymes, and inflammatory markers were assessed at baseline/fasting and 1, 2, and 4 hours after the HFM. Results: Addition of mango resulted in lower glucose (95.8 ± 4.4 mg/dL; P = .002) and higher high-density lipoprotein cholesterol (HDL-C; 58.4 ± 2.7 mg/dL; P = .01) 1 hour post-HFM compared to control (glucose: 104.8 ± 5.4 mg/dL; HDL-C: 55.2 ± 2.3 mg/dL), although no differences were observed in triglycerides ( P = .88 for interaction). No significant meal × time interactions were detected in markers of inflammation (C-reactive protein, P = .17; interleukin-6, P = .30) or antioxidant enzymes (superoxide dismutase, P = .77; glutathione peroxidase, P = .36; catalase, P = .32) in the postprandial period. Conclusions: When added to an HFM, acute mango consumption had modest beneficial effects on postprandial glucose and HDL-C responses, but did not alter triglyceride, inflammatory, or antioxidant enzymes.